The Development of an Ice-Ocean Coupled Model for the Northern Hemisphere. - Cheng, Abe; Preller, Ruth H. (1996)
The Polar Ice Prediction System (PIPS), based on the Hibler ice model, has been reformulated into spherical coordinates for the Northern Hemisphere. These spherical coordinates help to avoid a numerical singularity at the North Pole and numerical instabilities in high latitudes. Further, a coordinate transformation was chosen so that a new equator coincides with the 170 deg W - 10 deg E great circle, and a new north pole is located at the intersection of the 100 deg E meridian and the true Equator. The spherical coordinate PIPS model has been extended southward in a version of the model called PlPS2.0. In another development, the Cox ocean model has been transformed into the same spherical coordinate system as PIPS and then coupled with the sea ice model. The coupling technique of the ice and ocean models is conceptually similar to that described in Hibler and Bryan, but the heat and momentum exchanges have been modified. The two models are coupled by exchanging daily information of ice and ocean. The coupled model has been tested using the 1986 monthly forcing of the Navy Operational Global Atmospheric Prediction System (NOGAPS), as well as other inputs describing river runoff, bottom topography, and climatological water temperature and salinity. Preliminary results have been published. This report describes the coordinate transformation referred to above, the physics of the heat and momentum exchanges, model parameters, variable ice-water drag coefficients, and a test case using the 1986 monthly NOGAPS forcing fields. For the discussions in this report, the model domain was divided into seven subregions: the Sea of Okhotsk, the Bering Sea, the central Arctic, the Barents Sea, Hudson Bay, the Labrador Sea/Baffin Bay, and the Norwegian/East Greenland Seas. Prepared in collaboration with Sverdrup Technologies Inc., Stennis Space Center, MS.